Meningkatkan Kemampuan Mengenal Huruf Melalui Media Biji Kopi (PTK Di PAUD Sinar Kungkai Kabupaten Seluma) - Putriani, Desi; Margaretha, Lydia; Asnawati, Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the improvement in children's ability to recognise letters through the use of coffee beans at the Sinar Kungkai Early Childhood Education Centre in Seluma Regency. This study was a classroom action research (CAR) study using a cyclical procedure. The subjects of this study were 11 children in Group B at the Sinar Kungkai Early Childhood Education Centre. The research was conducted over two cycles, each consisting of two meetings. Data analysis was performed using both qualitative and quantitative descriptive methods, with the qualitative analysis focusing on determining the improvement in the process, expressed as a predicate, while the quantitative analysis was used to determine the improvement in outcomes using percentages. Based on the research results, the improvement in children's ability to recognise letters through the use of coffee beans as a teaching aid at PAUD Sinar Kungkai was as follows: in Cycle I, Session I, the percentage was 38.06%; in Cycle I, Session II, the percentage was 44.31%; in Cycle II, Session I, the percentage was 63.02%; and in Cycle II, Session II, the percentage was 81.81%. The conclusion of this study is that the use of coffee bean media in learning can improve children's ability to recognise letters at PAUD Sinar Kungkai in Seluma District, as evidenced by an increase in Cycle II Session II with a percentage achievement of 81.81% and a very good development criterion (BSB).